2010
DOI: 10.2174/187153010791213056
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Metabolic Syndrome

Abstract: Given the higher burden of risk factors for metabolic syndrome (MetS) on morbidity and mortality, it is critical to prevent the development of metabolic syndrome in the first place. While dietary habits have been favorably associated with some of the factors included in the definition of metabolic syndrome, limited and inconsistent data have been reported on the role of nutrition in the development of metabolic syndrome. Currently, there is no consensus as to which dietary patterns would confer the lowest risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 191 publications
(246 reference statements)
2
30
0
1
Order By: Relevance
“…This pattern is characterized by a diet rich in monounsaturated fatty acids (MUFA) from olives and olive oil; daily intake of whole grain cereals, fruits, vegetables, and dairy; and weekly intakes of fish, poultry, nuts, and legumes. Several studies have found the MDP to be associated with a lower MetS prevalence [21,22]. Moreover, a systematic review and meta-analysis of epidemiological studies and RCTs confirmed that adherence to a MDP was associated with reduced risk of MetS compared to control diets [23], as noted through beneficial effects on all individual criteria for the syndrome.…”
Section: Mets and The Mdpmentioning
confidence: 87%
See 3 more Smart Citations
“…This pattern is characterized by a diet rich in monounsaturated fatty acids (MUFA) from olives and olive oil; daily intake of whole grain cereals, fruits, vegetables, and dairy; and weekly intakes of fish, poultry, nuts, and legumes. Several studies have found the MDP to be associated with a lower MetS prevalence [21,22]. Moreover, a systematic review and meta-analysis of epidemiological studies and RCTs confirmed that adherence to a MDP was associated with reduced risk of MetS compared to control diets [23], as noted through beneficial effects on all individual criteria for the syndrome.…”
Section: Mets and The Mdpmentioning
confidence: 87%
“…Fruits and vegetables have been found to lower the risk of MetS and inflammation [21,39], as well as decrease BP [21]. Significant inverse associations between whole grain intake and MetS have been shown, independent of confounders including other dietary factors.…”
Section: Fruits Vegetables and Whole Grains As Components Of Mdp Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Pozitivan utjecaj cjelovitih žitarica pripisuje se niskom glikemijskom indeksu i sinergiji nutritivnih komponenti 3,4 .…”
Section: Sažetakunclassified